2019
DOI: 10.1111/jce.14183
|View full text |Cite
|
Sign up to set email alerts
|

Free thyroxine within the normal reference range predicts risk of atrial fibrillation

Abstract: Introduction: Hyperthyroidism is a known precipitating factor for atrial fibrillation (AF). However, recent reports have suggested an increased risk of AF with free thyroxine (fT4) levels even within the upper reference (normal) range. We sought to test whether higher fT4 levels within the reference range are associated with an increased risk of AF.Methods and Results: All patients in the Intermountain Healthcare electronic medical record database with an fT4 level not on thyroid medication were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Patients with long-standing overt hyperthyroidism with an increased cardiac output can predispose to AF occurrence [11]. It has been demonstrated that even subclinical hyperthyroidism is associated with an increased risk of AF [12-14]. Recent studies indicated that patients with a history of thyroid dysfunction (both hyperthyroidism and hypothyroidism) had a higher incidence of arrhythmia recurrence after AF catheter ablation [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with long-standing overt hyperthyroidism with an increased cardiac output can predispose to AF occurrence [11]. It has been demonstrated that even subclinical hyperthyroidism is associated with an increased risk of AF [12-14]. Recent studies indicated that patients with a history of thyroid dysfunction (both hyperthyroidism and hypothyroidism) had a higher incidence of arrhythmia recurrence after AF catheter ablation [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…The first is an analysis of 174,914 patients followed for 7.0 -4.9 years. It revealed that the incidence and prevalence of AF was greater with elevated serum fT4 levels, even within the normal reference range, but no relationship was noted for serum total T3 and fT3 within their normal reference ranges (62). The second study is an analysis of 55,114 individuals with AF and 482,295 referents.…”
Section: Pharmacodynamics Of Lt3 and Adrsmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia worldwide, affecting more than 30 million persons all over the globe [ 1 ]. Characterized by ever increasing prevalence and incidence rates, AF contributes significantly to morbidity and mortality through increased risk of stroke, heart failure and hospitalizations [ 2 ]. In particular, AF increases the risk of stroke by 5 folds; these strokes are of greater severity and lethality than those of their non-AF counterparts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Characterized by ever increasing prevalence and incidence rates, AF contributes significantly to morbidity and mortality through increased risk of stroke, heart failure and hospitalizations [ 2 ]. In particular, AF increases the risk of stroke by 5 folds; these strokes are of greater severity and lethality than those of their non-AF counterparts [ 2 ]. Despite its slightly increased prevalence in men, AF's adverse complications are more pronounced in women [ 3 ].…”
Section: Introductionmentioning
confidence: 99%